Polyfunctional MDI oligomers through dendrimerization - Martinelli, Marisa (2007)
An accessible pathway to synthesize dendronized MDI oligomers was studied. Two dendrons bearing –CN and –t-butyl functional groups on the periphery were obtained following the synthetic strategy proposed by Newkome et al. Dendrons with one focal point were converted from nitro into amino precursors and used as modifiers in the preparation of new functionalized materials. The coupling reaction of dendrons on oligomers with isocyanate groups was carried out through an easy and quick procedure. The dendronized oligomers showed conformation changes according to the polarity of the solvents, allowing a prediction of a “stimuli-responsive” behavior.